Pouched Rats' Detection of Tuberculosis in Human Sputum: Comparison to Culturing and Polymerase Chain Reaction. (9th July 2012) - Mahoney, Amanda; Weetjens, Bart J.; Cox, Christophe; Beyene, Negussie; Reither, Klaus; Makingi, George; Jubitana, Maureen; Kazwala, Rudovick; Mfinanga, Godfrey S.; Kahwa, Amos; Durgin, Amy; Poling, Alan
Abstract : Setting . Tanzania. Objective . To compare microscopy as conducted in direct observation of treatment, short course centers to pouched rats as detectors of Mycobacterium tuberculosis . Design . Ten pouched rats were trained to detect tuberculosis in sputum using operant conditioning techniques. The rats evaluated 910 samples previously evaluated by smear microscopy. All samples were also evaluated through culturing and multiplex polymerase chain reaction was performed on culture growths to classify the bacteria. Results . The patientwise sensitivity of microscopy was 58.0%, and the patient-wise specificity was 97.3%. Used as a group of 10 with a cutoff (defined as the number of rat indications to classify a sample as positive for Mycobacterium tuberculosis ) of 1, the rats increased new case detection by 46.8% relative to microscopy alone. The average samplewise sensitivity of the individual rats was 68.4% (range 61.1–73.8%), and the mean specificity was 87.3% (range 84.7–90.3%). Conclusion . These results suggest that pouched rats are a valuable adjunct to, and may be a viable substitute for, sputum smear microscopy as a tuberculosis diagnostic in resource-poor countries.